Inhuman intelligence. The evolution of Human Rights - Pérez Brito, Raquel Lucía (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2021)
The debate on scientific advances and their effects goes beyond national borders. Real power has shifted from States to private companies that globally control technological development, big data and the knowledge society, thus interfering in people’s lives. For this reason, a legislative development with a universal vocation and defined ethical codes that takes into account the development of Inhuman Intelligence is created by and for the betterment of humanity. The “right to life” must be placed on an ontological level higher than any other universal right to guarantee the survival of the human being and reach a “fully human Era” as opposed to transhumanist currents headed for a “post-humanist Era”.